Screening and identification of hepatotoxic component in Evodia rutaecarpa based on spectrum–effect relationship and UPLC‐Q‐TOFMS. (28th June 2016) - Li, Wenlan; Sun, Xiangming; Liu, Bingmei; Zhang, Lihui; Fan, Ziquan; Ji, Yubin
Abstract: Evodia rutaecarpa ( E. rutaecarpa ) has been used to treat aches, vomiting and dysentery in traditional Chinese medicine. However, as a mildly toxic herb its toxic components have not been elucidated. An attempt was made to illuminate the hepatotoxic constituents of E. rutaecarpa . The 50% ethanol extracts of E. rutaecarpa from 19 different sources were used to establish UPLC fingerprints and administered to mice at a dose of 35 g/kg (crude medicine weight/mouse weight) once daily for 14 days. Serum levels of alanine transaminase, aspartate aminotransferase and liver coefficient were used as indices of liver injury. Additionally, the characteristic peaks of 19 fingerprints were identified. Spectrum–effect relationships between fingerprints and hepatotoxic indicators were analyzed using bivariate correlation analysis (BCA). The UPLC fingerprints were established and a total of 28 main compounds were identified. Because of the inherent variations in chemical compositions, the liver injury levels were different among the E. rutaecarpa samples from 19 sites of production. BCA results indicated that compounds dihydrorutaecarpine, 6‐acetoxy‐5‐epilimonin, goshuyuamide I, 1‐methyl‐2‐[( Z )‐5‐undecenyl]‐4(1H)‐quinolone, 1‐methyl‐2‐[(4 Z, 7Z)‐4, 7‐tridecadienyl]‐4(1H)‐quinolone, evocarpine and 1‐methyl‐2‐[(6 Z, 9 Z )‐6, 9‐pentadecadienyl]‐4(1H)‐quinolone were tentatively determined as the primary hepatotoxic components. The present study provides a valuable method for the discovery of hepatotoxic constituents by combination of fingerprints and hepatotoxicity index.